Utilization Of Soybean Hull Flour As A Substitute In White Bread - Antonny Alexander Bertrand Wijanto; Jason Lau; Hari Minantyo (Universitas Negeri Padang, 2026)
This study aimed to evaluate the effect of soybean hull flour substitution on the sensory characteristics and fiber content of white bread. The research employed an experimental method using a Completely Randomized Design (CRD) with substitution levels of 0%, 5%, 10%, and 15% using oven and dehydrator drying methods. Organoleptic testing was conducted with 30 untrained panelists and three repetitions to evaluate color, aroma, texture, and taste using a Likert scale. Data were analyzed using ANOVA to determine the effect of substitution and processing methods on sensory characteristics.The results showed that soybean hull flour substitution significantly affected the sensory characteristics of white bread, particularly taste and texture. The best formulation was obtained from the 5% substitution with the oven method (OV1), which achieved the highest level of panelist acceptance. Soybean hull flour substitution also increased dietary fiber content from 0,729% in the control bread to 2,28 % in the substituted bread. Based on SNI 8371:2018 standards and nutritional claim regulations by the National Food Agency, these results indicate that the substituted bread has the potential to be developed as a high-fiber food product. However, higher substitution levels (10%–15%) produced a denser texture and reduced bread volume expansion. This study was limited to organoleptic testing using untrained panelists in a single testing location within a limited community setting. Overall, soybean hull flour has potential as a functional food ingredient in high-fiber white bread products.